Influence of Percentage Replacement of Metakaolin on Different Concrete Types Exposed to Internal Sulphate Attack - K. Awad, Hadeel; K. Aboud, Rawaa; D. Mohammed, Shatha (International Journal of Engineering and Technology, 2018)
This research presents an experimental investigation on the influence of metakaolin replacement percentage upon some properties of       different concrete types. Three types of concrete were adopted (self- compacted concrete, high performance concrete and reactive powder concrete) all of high sulphate (SO3) percentage from the fine aggregate weight, 0.75%.Three percentages of metakaolin replacement were selected to be studied (5, 7 and 10) %. Three types of concrete properties (compressive, flexural and splitting tensile strength) were adopted to achieve better understanding for the influence of adding metakaolin.. The output results indicated that the percentage of metakaolin had a different level of positive effect on the compressive strength for both including and excluding of internal sulphate attack. This effect reached at 28 days of curing to (11.86, 10.22 and 4.75) % in case of excluding sulphate attack and to (13.82, 11.47and 6.53) % in the other case for SCC, HPC and RPC respectively. It can be concluded that the effect of metakaolin in both SCC and HPC are more influence than in RPC. Splitting and flexural strength have showed a similar behavior, flexural strength increased by (15.38, 9.42 and 5,84) % at age of 28 days when the sulphate attack is excluded, while it was (14.02, 10.66 and 4.28)% in case of sulphate attack included for SCC,HPC and RPC respectively. The response of splitting tensile strength for both including and excluding of sulphate attack reached to (13.03, 12.95 and 9.17) % and (16.88, 10.33 and 6.74) % respectively for SCC, HPC and RPC.
Keywords: High performance concrete; internal sulphate attack; metakaolin; reactive powder concrete and self-compacted concrete.